A high temperature thermal shock resistant ceramic crucible and preparation method thereof
By combining specific specifications of ceramic powder with nano-silicon sol and additives, a high-temperature thermal shock resistance ceramic crucible is prepared, which solves the problems of poor high-temperature thermal shock resistance, short service life and environmental pollution of existing ceramic crucibles, and achieves efficient preparation and excellent performance of ceramic crucibles.
Patent Information
- Application Number
- CN202411537965.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing ceramic crucibles have environmental pollution problems caused by poor high temperature thermal shock resistance, short service life, poor corrosion resistance, uneven wall thickness, and high organic content during preparation.
The first ceramic slurry is prepared by combining a specific specification of ceramic powder with a nano-silicon sol and an additive through a ball mill mixing and dispersion, and then combined with the second ceramic powder with a specific raw material composition and particle grading to prepare the finished product slurry. Then, in the green molding step, low-pressure injection and high-pressure injection are combined, and finally, after a three-stage firing treatment of a specific heating rate and temperature, a high-temperature thermal shock-resistant ceramic crucible is prepared.
It improves the high-temperature thermal shock resistance, corrosion resistance and service life of the ceramic crucible, and makes the wall thickness uniform and the appearance clean and delicate, while reducing the organic content during the preparation process and reducing environmental pollution.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of ceramic crucibles, and in particular to a high-temperature thermal shock resistant ceramic crucible and a preparation method thereof. Background Art
[0002] In recent decades, aerospace smelting materials have developed rapidly. Due to the need to melt refractory metals, special alloys, ultra-pure metals, etc., the demand for high-temperature thermal shock resistant ceramic crucibles has increased dramatically and has long occupied an important position. As the basic melting equipment for special alloys, high-temperature thermal shock resistant ceramic crucibles must constantly withstand cold and hot shocks and slag erosion of smelting materials during use, and require good thermal shock stability, corrosion resistance and spalling resistance. In addition, with the promotion and application of new aviation technologies and the commissioning of large-scale, continuous and efficient advanced equipment for the preparation of aerospace smelting materials, the working conditions of high-temperature thermal shock resistant ceramic crucibles have deteriorated, and higher performance requirements have been put forward for them.
[0003] At present, the existing ceramic crucibles have the problems of poor high-temperature thermal shock resistance, short service life, poor erosion resistance, and uneven wall thickness, which seriously restrict the development of aviation material research. Based on this, providing a ceramic crucible with good high-temperature thermal shock resistance, good erosion resistance, long service life, uniform wall thickness, clean and delicate appearance, has important value and technical significance for the smelting and research and development of aerospace materials.
[0004] Furthermore, the existing method for preparing high-temperature thermal shock resistant ceramic crucibles requires the use of a large amount of organic raw materials to ensure the performance of the ceramic crucible. There is a problem of high organic content in the preparation process, which directly leads to great environmental pollution during the sintering process and poor environmental friendliness. Summary of the invention
[0005] In order to solve the technical problems existing in the prior art, the present invention provides a high-temperature thermal shock resistant ceramic crucible and a preparation method thereof, which can improve the high-temperature thermal shock resistance, corrosion resistance and service life of the ceramic crucible while improving the uniformity of the wall thickness of the ceramic crucible, and the appearance of the ceramic crucible is clean and delicate; and further overcomes the environmental pollution problem caused by the high organic content in the existing ceramic crucible preparation method.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a high-temperature thermal shock resistant ceramic crucible comprises the following steps: preparing a first ceramic slurry, preparing a finished product slurry, green body molding, and solidifying and sintering.
[0008] The method for preparing the first ceramic slurry is to mix and disperse the first ceramic powder, nano-silica sol, dispersant, defoamer, water reducer and binder through ball milling, control the ball-to-material ratio to be 2.2-2.5:1, water-cool the ball mill tank when the ball milling temperature exceeds 25°C, the ball milling speed is 30-50r / min, and the ball milling time is 12-18h to obtain the first ceramic slurry.
[0009] In the preparation of the first ceramic slurry, the first ceramic powder is composed of the following raw materials: alumina powder, 325 mesh plate-shaped corundum powder, 1250 mesh fused quartz powder, light-burned magnesia-alumina spinel, and kaolin.
[0010] Preferably, the concentration of nano silica sol is 20-25wt%;
[0011] The dispersant is at least one of the following: ammonium polyacrylate, ammonium citrate, polyvinyl carboxylic acid;
[0012] The defoamer is at least one of the following: an organosilicon defoamer, a polyether defoamer, or a polyether-modified silicon defoamer;
[0013] The water reducing agent is water glass;
[0014] The binder is a carboxymethyl cellulose (CMC) aqueous solution, and the weight ratio of the carboxymethyl cellulose to water is 1:4.8-5.2.
[0015] Preferably, the weight ratio of alumina powder, 325 mesh plate-shaped corundum powder, 1250 mesh fused quartz powder, light-burned magnesia-alumina spinel, kaolin, nano-silica sol, dispersant, defoamer, water reducer and binder is 20-30:10-15:8-15:15-25:3-5:5-10:0.3-0.8:0.1-0.3:0.3-0.5:25-35.
[0016] The method for preparing the finished slurry is as follows: sieving the first ceramic slurry and pouring it into an empty ball mill for aging, controlling the ball mill speed to 18-20 r / min, the aging temperature to 15-25°C, the relative humidity to 35-60%, and the aging time to 24-30h, and after the aging is completed, continuing to add the second ceramic powder to obtain a premix; pouring the premix into a vertical stirring tank, controlling the stirring speed to 20-30 r / min, the stirring temperature to 35-40°C, and the stirring time to 3-5h to obtain a finished slurry.
[0017] In the prepared finished slurry, the second ceramic powder is composed of the following raw materials: 30-50 mesh fused quartz powder, 50-100 mesh fused quartz powder, 80-200 mesh fused quartz powder, 80-150 mesh plate-shaped corundum powder; the weight ratio of 30-50 mesh fused quartz powder, 50-100 mesh fused quartz powder, 150-200 mesh fused quartz powder, and 80-150 mesh plate-shaped corundum powder is 8-12:6-10:3-5:10-15;
[0018] The weight ratio of the first ceramic powder to the second ceramic powder is 60-80:20-40.
[0019] The green body molding method comprises the following steps: pouring the finished slurry into a high-pressure grouting machine for casting and molding; firstly controlling the injection pressure to 0.2-0.3MPa, the injection flow rate to 250-400mL / min, and low-pressure injection for 40-60s to fill 5-10% of the volume of the mold; then controlling the injection pressure to 0.9-1.0MPa, the injection flow rate to 900-1200mL / min, and high-pressure injection for 180-300s to fill the mold; and then maintaining the pressure for 900-1200s to remove the mold to obtain the ceramic crucible green body.
[0020] The curing and firing method comprises the following steps: placing a ceramic crucible green body in an environment with a temperature of 20-26° C. and a relative humidity of 40-70%, and performing constant temperature and humidity curing for 48 hours or more to obtain a ceramic crucible blank; trimming the ceramic crucible blank and placing it in an oven, and drying it at 110-120° C. for 24 hours or more to obtain a ceramic crucible blank; placing the ceramic crucible blank in a firing furnace, controlling the heating rate to be 45-50° C. / h, heating it to 240-250° C., and keeping it warm for one time and firing it for 2.5-3 hours; controlling the heating rate to be 75-80° C. / h, heating it to 640-650° C., and keeping it warm for two times and firing it for 2-2.5 hours; controlling the heating rate to be 245-250° C. / h, heating it to 1180-1230° C., and keeping it warm for three times and firing it for 3-5 hours, and then cooling it to obtain a high-temperature thermal shock resistant ceramic crucible.
[0021] A high-temperature thermal shock resistant ceramic crucible is prepared by the above-mentioned preparation method.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1) The preparation method of the high-temperature thermal shock resistant ceramic crucible of the present invention comprises the following steps: using a first ceramic powder composed of raw materials of specific specifications, combining it with silica sol and an additive to obtain a first ceramic slurry, and then combining it with a second ceramic powder of specific raw material composition and particle size distribution to obtain a finished slurry; then in the green body forming step, low-pressure injection and high-pressure injection are combined to obtain a ceramic crucible green body; after the ceramic crucible green body is cured and dried, it is subjected to a three-stage sintering treatment at a specific heating rate and temperature to obtain a high-temperature thermal shock resistant ceramic crucible; the aforementioned technical means cooperate and work synergistically with each other, which can improve the high-temperature thermal shock resistance, corrosion resistance and service life of the ceramic crucible while improving the uniformity of the wall thickness of the ceramic crucible, and the appearance of the ceramic crucible is clean and delicate; and further overcome the environmental pollution problem caused by the high organic content in the existing ceramic crucible preparation method.
[0024] 2) The high temperature thermal shock resistant ceramic crucible of the present invention has uniform wall thickness, clean and delicate appearance, controllable sintering consistency, and a bulk density of 2.51-2.55 g / cm 3 The apparent porosity is 18.5-19.8%, the compressive strength at room temperature is 101.4-102.7MPa, the flexural strength at 1300℃ is 15.3-16.5MPa, the mass loss rate of acid corrosion is 0.08-0.09%, the mass loss rate of alkali corrosion is 0.07-0.08%, and the roughness Ra is 3.168-3.186um.
[0025] 3) After 10 thermal shock cycles (1600°C, air cooling), the high-temperature thermal shock resistant ceramic crucible of the present invention has no cracks; the effective thermal shock resistance of the ceramic crucible can reach 13 times, and the ceramic crucible has good thermal shock resistance and can meet the use requirements of repeated casting of special high-temperature alloys.
[0026] 4) In the preparation process of the high-temperature thermal shock resistant ceramic crucible of the present invention, the organic raw material content is low and the specific raw materials are combined, which can shorten the firing cycle, improve production efficiency, reduce production energy consumption and cost, and effectively reduce environmental pollution. The preparation method is highly environmentally friendly. DETAILED DESCRIPTION
[0027] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0028] Example 1
[0029] This embodiment provides a method for preparing a high-temperature thermal shock resistant ceramic crucible, specifically:
[0030] 1. Preparation of the first ceramic slurry
[0031] The first ceramic powder, nano-silica sol, dispersant, defoamer, water reducer and binder are mixed and dispersed by ball milling, and the ball-to-material ratio is controlled to be 2.3:1. When the ball milling temperature exceeds 25°C, the ball mill tank is water-cooled, the ball milling speed is 40r / min, and the ball milling time is 16h to obtain the first ceramic slurry.
[0032] The first ceramic powder is composed of the following raw materials: alumina powder, 325 mesh plate-shaped corundum powder, 1250 mesh fused quartz powder, light-burned magnesia-alumina spinel, and kaolin.
[0033] The concentration of nano-silica sol is 22wt%.
[0034] The dispersants are ammonium polyacrylate and ammonium citrate; the weight ratio of ammonium polyacrylate to ammonium citrate is 3:1.
[0035] The defoaming agent is a polyether defoaming agent.
[0036] The water reducing agent is water glass.
[0037] The binder is a carboxymethyl cellulose (CMC) aqueous solution, and the weight ratio of the carboxymethyl cellulose to water is 1:5.
[0038] The weight ratio of alumina micropowder, 325 mesh plate-shaped corundum powder, 1250 mesh fused quartz powder, light-burned magnesia-alumina spinel, kaolin, nano-silica sol, dispersant, defoamer, water reducer and binder is 25:13:12:20:4:7:0.5:0.2:0.4:29.
[0039] 2. Prepare finished slurry
[0040] After sieving the first ceramic slurry, pour it into an empty ball mill for aging. Control the ball mill speed to 19 r / min, the aging temperature to 20°C, the relative humidity to 50%, and the aging time to 28 h. After the aging is completed, continue to add the second ceramic powder to obtain a premix. Pour the premix into a vertical mixing tank, control the stirring speed to 25 r / min, the stirring temperature to 38°C, and the stirring time to 4 h to obtain a finished slurry.
[0041] Among them, the second ceramic powder is composed of the following raw materials: 30-50 mesh fused quartz powder, 50-100 mesh fused quartz powder, 80-200 mesh fused quartz powder, and 80-150 mesh plate-like corundum powder; the weight ratio of 30-50 mesh fused quartz powder, 50-100 mesh fused quartz powder, 150-200 mesh fused quartz powder, and 80-150 mesh plate-like corundum powder is 10:8:4:13.
[0042] The weight ratio of the first ceramic powder to the second ceramic powder is 70:30.
[0043] 3. Green forming
[0044] The finished slurry is poured into a high-pressure grouting machine for casting and molding. First, the injection pressure is controlled to 0.2MPa, the injection flow rate is 320mL / min, and the low-pressure injection is performed for 50s to fill 8% of the mold volume; then the injection pressure is controlled to 0.9MPa, the injection flow rate is 1000mL / min, and the high-pressure injection is performed for 240s to fill the mold; then the pressure is maintained for 1100s, and the ceramic crucible green body is removed from the mold.
[0045] 4. Curing and firing
[0046] The ceramic crucible green body is placed in an environment with a temperature of 24°C and a relative humidity of 60%, and maintained at a constant temperature and humidity for 48 hours to obtain a ceramic crucible blank; the ceramic crucible blank is trimmed and placed in an oven, and dried at 115°C for 24 hours to obtain a ceramic crucible blank; the ceramic crucible blank is placed in a sintering furnace, and the heating rate is controlled to be 50°C / h, the temperature is increased to 250°C, and the temperature is kept warm for 3 hours; the heating rate is controlled to be 80°C / h, the temperature is increased to 650°C, and the temperature is kept warm for 2 hours; the heating rate is controlled to be 250°C / h, the temperature is increased to 1200°C, and the temperature is kept warm for 4 hours, and then cooled to obtain a high-temperature thermal shock resistant ceramic crucible with uniform wall thickness and clean and delicate appearance.
[0047] This embodiment also provides a high-temperature thermal shock resistant ceramic crucible made by the aforementioned method.
[0048] Example 2
[0049] This embodiment provides a method for preparing a high-temperature thermal shock resistant ceramic crucible, specifically:
[0050] 1. Preparation of the first ceramic slurry
[0051] The first ceramic powder, nano-silica sol, dispersant, defoamer, water reducer and binder are mixed and dispersed by ball milling, and the ball-to-material ratio is controlled to be 2.2:1. When the ball milling temperature exceeds 25°C, the ball mill tank is water-cooled, the ball milling speed is 30rpm, and the ball milling time is 12h to obtain the first ceramic slurry.
[0052] The first ceramic powder is composed of the following raw materials: alumina powder, 325 mesh plate-shaped corundum powder, 1250 mesh fused quartz powder, light-burned magnesia-alumina spinel, and kaolin.
[0053] The concentration of nano-silica sol is 20wt%.
[0054] The dispersant is polyvinyl carboxylic acid.
[0055] The defoamer is a polyether modified silicone defoamer.
[0056] The water reducing agent is water glass.
[0057] The binder is a carboxymethyl cellulose (CMC) aqueous solution, and the weight ratio of the carboxymethyl cellulose to water is 1:4.8.
[0058] The weight ratio of alumina micropowder, 325 mesh plate-shaped corundum powder, 1250 mesh fused quartz powder, light-burned magnesia-alumina spinel, kaolin, nano-silica sol, dispersant, defoamer, water reducer and binder is 20:10:8:15:3:5:0.3:0.1:0.3:25.
[0059] 2. Prepare finished slurry
[0060] After sieving the first ceramic slurry, pour it into an empty ball mill for aging. Control the ball mill speed to 18 r / min, the aging temperature to 15°C, the relative humidity to 35%, and the aging time to 24 h. After the aging is completed, continue to add the second ceramic powder to obtain a premix. Pour the premix into a vertical stirring tank, control the stirring speed to 20 r / min, the stirring temperature to 35°C, and the stirring time to 3 h to obtain a finished slurry.
[0061] Among them, the second ceramic powder is composed of the following raw materials: 30-50 mesh fused quartz powder, 50-100 mesh fused quartz powder, 80-200 mesh fused quartz powder, and 80-150 mesh plate-like corundum powder; the weight ratio of 30-50 mesh fused quartz powder, 50-100 mesh fused quartz powder, 150-200 mesh fused quartz powder, and 80-150 mesh plate-like corundum powder is 8:6:3:10.
[0062] The weight ratio of the first ceramic powder to the second ceramic powder is 60:40.
[0063] 3. Green forming
[0064] The finished slurry is poured into a high-pressure grouting machine for casting and molding. First, the injection pressure is controlled to 0.25MPa, the injection flow rate is 250mL / min, and the low-pressure injection is performed for 40s to fill 5% of the mold volume; then the injection pressure is controlled to 0.95MPa, the injection flow rate is 900mL / min, and the high-pressure injection is performed for 180s to fill the mold; then the pressure is maintained for 900s, and the ceramic crucible green body is removed from the mold.
[0065] 4. Curing and firing
[0066] The ceramic crucible green body is placed in an environment with a temperature of 20°C and a relative humidity of 40%, and maintained at a constant temperature and humidity for 54 hours to obtain a ceramic crucible blank; the ceramic crucible blank is trimmed and placed in an oven, and dried at 110°C for 30 hours to obtain a ceramic crucible blank; the ceramic crucible blank is placed in a sintering furnace, and the heating rate is controlled to be 45°C / h, the temperature is raised to 240°C, and the temperature is kept for 2.5 hours; the heating rate is controlled to be 75°C / h, the temperature is raised to 640°C, and the temperature is kept for 2 hours; the heating rate is controlled to be 245°C / h, the temperature is raised to 1180°C, and the temperature is kept for 3 hours, and then cooled to obtain a high-temperature thermal shock resistant ceramic crucible with uniform wall thickness and clean and delicate appearance.
[0067] This embodiment also provides a high-temperature thermal shock resistant ceramic crucible made by the aforementioned method.
[0068] Example 3
[0069] This embodiment provides a method for preparing a high-temperature thermal shock resistant ceramic crucible, specifically:
[0070] 1. Preparation of the first ceramic slurry
[0071] The first ceramic powder, nano-silica sol, dispersant, defoamer, water reducer and binder are mixed and dispersed by ball milling, and the ball-to-material ratio is controlled to be 2.5:1. When the ball milling temperature exceeds 25°C, the ball mill tank is water-cooled, the ball milling speed is 50r / min, and the ball milling time is 18h to obtain the first ceramic slurry.
[0072] The first ceramic powder is composed of the following raw materials: alumina powder, 325 mesh plate-shaped corundum powder, 1250 mesh fused quartz powder, light-burned magnesia-alumina spinel, and kaolin.
[0073] The concentration of nano-silica sol is 25wt%.
[0074] The dispersant is ammonium polyacrylate.
[0075] The defoaming agent is a polyether defoaming agent.
[0076] The water reducing agent is water glass.
[0077] The binder is a carboxymethyl cellulose (CMC) aqueous solution, and the weight ratio of the carboxymethyl cellulose to water is 1:5.2.
[0078] The weight ratio of alumina micropowder, 325 mesh plate-shaped corundum powder, 1250 mesh fused quartz powder, light-burned magnesia-alumina spinel, kaolin, nano-silica sol, dispersant, defoamer, water reducer and binder is 30:15:15:25:5:10:0.8:0.3:0.5:35.
[0079] 2. Prepare finished slurry
[0080] After sieving the first ceramic slurry, pour it into an empty ball mill for aging. Control the ball mill speed to 20 r / min, the aging temperature to 25°C, the relative humidity to 60%, and the aging time to 30 h. After the aging is completed, continue to add the second ceramic powder to obtain a premix. Pour the premix into a vertical stirring tank, control the stirring speed to 30 r / min, the stirring temperature to 40°C, and the stirring time to 5 h to obtain a finished slurry.
[0081] Among them, the second ceramic powder is composed of the following raw materials: 30-50 mesh fused quartz powder, 50-100 mesh fused quartz powder, 80-200 mesh fused quartz powder, and 80-150 mesh plate-like corundum powder; the weight ratio of 30-50 mesh fused quartz powder, 50-100 mesh fused quartz powder, 150-200 mesh fused quartz powder, and 80-150 mesh plate-like corundum powder is 12:10:5:15.
[0082] The weight ratio of the first ceramic powder to the second ceramic powder is 80:20.
[0083] 3. Green forming
[0084] The finished slurry is poured into a high-pressure grouting machine for casting and molding. First, the injection pressure is controlled to 0.3 MPa, the injection flow rate is 400 mL / min, and the low-pressure injection is performed for 60 seconds to fill 10% of the mold volume; then the injection pressure is controlled to 1.0 MPa, the injection flow rate is 1200 mL / min, and the high-pressure injection is performed for 300 seconds to fill the mold; then the pressure is maintained for 1200 seconds, and the ceramic crucible green body is removed from the mold.
[0085] 4. Curing and firing
[0086] The ceramic crucible green body is placed in an environment with a temperature of 26°C and a relative humidity of 70%, and maintained at a constant temperature and humidity for 48 hours to obtain a ceramic crucible blank; the ceramic crucible blank is trimmed and placed in an oven, and dried at 120°C for 24 hours to obtain a ceramic crucible blank; the ceramic crucible blank is placed in a sintering furnace, and the heating rate is controlled to be 48°C / h, the temperature is increased to 245°C, and the temperature is kept for one time and sintered for 2.75 hours; the heating rate is controlled to be 78°C / h, the temperature is increased to 645°C, and the temperature is kept for a second time and sintered for 2.25 hours; the heating rate is controlled to be 248°C / h, the temperature is increased to 1230°C, and the temperature is kept for three times and sintered for 5 hours, and then cooled to obtain a high-temperature thermal shock resistant ceramic crucible with uniform wall thickness and clean and delicate appearance.
[0087] This embodiment also provides a high-temperature thermal shock resistant ceramic crucible made by the aforementioned method.
[0088] The volume density, apparent porosity, room temperature compressive strength, 1300°C flexural strength, acid corrosion mass loss rate, alkali corrosion mass loss rate, and roughness of the high temperature thermal shock resistant ceramic crucibles of Examples 1-3 were tested respectively. Among them, the acid corrosion mass loss rate is to place the ceramic crucible in a 20wt% sulfuric acid solution, heat it to 90°C, keep it warm for 2h, and calculate the mass loss rate after acid corrosion. The alkali corrosion mass loss rate is to place the ceramic crucible in a 1wt% sodium hydroxide solution, heat it to 90°C, keep it warm for 2h, and calculate the mass loss rate after alkali corrosion.
[0089] The specific results are shown in the following table:
[0090]
[0091] Furthermore, the high-temperature thermal shock resistant ceramic crucibles of Examples 1-3 were respectively placed in an electric furnace, and in an air atmosphere environment, the temperature was increased to 1600°C at a heating rate of 50°C / min. After keeping warm for 0.5h, the temperature was cooled to room temperature by air. The aforementioned rapid heating and air cooling process was regarded as one thermal shock cycle. After 10 consecutive thermal shock cycles, the ceramic crucibles were observed to see if cracks appeared. Then, the aforementioned thermal shock cycle was continued until comminutive through cracks appeared in the ceramic crucible, and the effective number of thermal shock resistance was recorded (the effective number of thermal shock resistance was the total number of thermal shock cycles minus one).
[0092] The specific results are shown in the following table:
[0093]
[0094] It can be seen that the preparation method of the high-temperature thermal shock resistant ceramic crucible of the present invention adopts a first ceramic powder composed of raw materials of specific specifications, combines it with silica sol and additives to obtain a first ceramic slurry, and then combines it with a second ceramic powder with a specific raw material composition and particle grading to obtain a finished slurry; then in the green body forming step, low-pressure injection and high-pressure injection are combined to obtain a ceramic crucible green body; after the ceramic crucible green body is cured and dried, it is subjected to a three-stage sintering treatment at a specific heating rate and temperature to obtain a high-temperature thermal shock resistant ceramic crucible; the aforementioned technical means cooperate and work synergistically with each other, which can improve the high-temperature thermal shock resistance, corrosion resistance and service life of the ceramic crucible while improving the uniformity of the wall thickness of the ceramic crucible, and the appearance of the ceramic crucible is clean and delicate; and further overcome the environmental pollution problem caused by the high organic content in the existing ceramic crucible preparation method.
[0095] Unless otherwise specified, all percentages used in the present invention are by mass.
[0096] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high temperature thermal shock resistant ceramic crucible, characterized in that: The method comprises the following steps: preparing a first ceramic slurry, preparing a finished product slurry, green body molding, and curing and firing; The method for preparing the first ceramic slurry is to mix the first ceramic powder, nano silica sol, dispersant, defoamer, water reducer and binder by ball milling to obtain the first ceramic slurry; The first ceramic powder is composed of the following raw materials: alumina powder, 325 mesh plate-shaped corundum powder, 1250 mesh fused quartz powder, light-burned magnesia-alumina spinel, and kaolin; In the preparation of the first ceramic slurry, the weight ratio of alumina powder, 325 mesh plate-shaped corundum powder, 1250 mesh fused quartz powder, light-burned magnesium aluminum spinel, kaolin, nano silica sol, dispersant, defoamer, water reducer, and binder is 20-30:10-15:8-15:15-25:3-5:5-10:0.3-0.8:0.1-0.3:0.3-0.5:25-35; The method for preparing the finished slurry comprises: sieving the first ceramic slurry and then aging it, and then adding the second ceramic powder to obtain a premix after the aging is completed; and mixing the premix evenly to obtain the finished slurry; The second ceramic powder is composed of the following raw materials: 30-50 mesh fused quartz powder, 50-100 mesh fused quartz powder, 80-200 mesh fused quartz powder, and 80-150 mesh plate-shaped corundum powder; in the second ceramic powder, the weight ratio of 30-50 mesh fused quartz powder, 50-100 mesh fused quartz powder, 150-200 mesh fused quartz powder, and 80-150 mesh plate-shaped corundum powder is 8-12:6-10:3-5:10-15; The weight ratio of the first ceramic powder to the second ceramic powder is 60-80:20-40; The green body molding method comprises the following steps: using the finished slurry for casting molding, firstly controlling the injection pressure to be 0.2-0.3 MPa, injecting the slurry into the mold at low pressure to fill 5-10% of the volume of the mold; then controlling the injection pressure to be 0.9-1.0 MPa, injecting the slurry into the mold at high pressure to fill the mold; then maintaining the pressure, and removing the slurry from the mold to obtain the ceramic crucible green body; The solidification and firing method comprises the following steps: after curing and drying the green ceramic crucible, the green ceramic crucible is placed in a firing furnace, the heating rate is controlled to be 45-50°C / h, the temperature is raised to 240-250°C, the temperature is kept at this temperature for one firing; the heating rate is controlled to be 75-80°C / h, the temperature is raised to 640-650°C, the temperature is kept at this temperature for two firings; the heating rate is controlled to be 245-250°C / h, the temperature is raised to 1180-1230°C, the temperature is kept at this temperature for three firings, and the green ceramic crucible is cooled to obtain a high-temperature thermal shock resistant ceramic crucible.
2. The method for preparing a high temperature thermal shock resistant ceramic crucible according to claim 1, characterized in that: In the preparation of the first ceramic slurry, the ball-to-cement ratio is controlled to be 2.2-2.5:1, the ball milling speed is 30-50 r / min, and the ball milling time is 12-18 h.
3. The method for preparing a high temperature thermal shock resistant ceramic crucible according to claim 1, characterized in that: In the preparation of the first ceramic slurry, the dispersant is at least one of the following: ammonium polyacrylate, ammonium citrate, polyvinyl carboxylic acid; The defoamer is at least one of the following: an organosilicon defoamer, a polyether defoamer, and a polyether-modified silicon defoamer.
4. The method for preparing a high temperature thermal shock resistant ceramic crucible according to claim 1, characterized in that: In the preparation of the first ceramic slurry, the concentration of nano-silica sol is 20-25wt%; The water reducing agent is water glass; The binder is a carboxymethyl cellulose aqueous solution, and the weight ratio of the carboxymethyl cellulose to water in the binder is 1:4.8-5.
2.
5. The method for preparing a high temperature thermal shock resistant ceramic crucible according to claim 1, characterized in that: In the preparation of the finished slurry, the ball mill speed is controlled to be 18-20r / min, the aging temperature is 15-25°C, the relative humidity is 35-60%, and the aging time is 24-30h during the aging process; During the mixing process of the premix, the stirring speed is controlled at 20-30 r / min, the stirring temperature is 35-40°C, and the stirring time is 3-5h.
6. The method for preparing a high temperature thermal shock resistant ceramic crucible according to claim 1, characterized in that: In the green body molding, the injection flow rate of the low-pressure injection mold is 250-400 mL / min, and the low-pressure injection time is 40-60 s; The injection flow rate of the high-pressure injection mold is 900-1200mL / min, and the high-pressure injection time is 180-300s; The holding time is 900-1200s.
7. The method for preparing a high temperature thermal shock resistant ceramic crucible according to claim 1, characterized in that: During the curing and firing, the curing temperature is 20-26°C, the curing relative humidity is 40-70%, and the constant temperature and humidity curing time is 48 hours or more; The insulation time for the first firing is 2.5-3h; the insulation time for the second firing is 2-2.5h, and the insulation time for the third firing is 3-5h.
8. A high temperature thermal shock resistant ceramic crucible, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Hollow plate full-ceramic filter membrane element and preparation process method thereof
CN106621846A
Wear-resisting ceramic product and manufacturing technology thereof
CN107555948A